2012
DOI: 10.1016/b978-0-12-394305-7.00001-x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Functions of Tissue Transglutaminase

Abstract: Transglutaminase 2 (TG2 or tissue transglutaminase) is a highly complex multifunctional protein that acts as transglutaminase, GTPase/ATPase, protein disulfide isomerase, and protein kinase. Moreover, TG2 has many well-documented nonenzymatic functions that are based on its noncovalent interactions with multiple cellular proteins. A vast array of biochemical activities of TG2 accounts for its involvement in a variety of cellular processes, including adhesion, migration, growth, survival, apoptosis, differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
271
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(273 citation statements)
references
References 412 publications
(838 reference statements)
2
271
0
Order By: Relevance
“…TG2 can catalyse two types of transamidation, namely (i) intra-, and/or inter-molecular covalent cross-links between protein-bound glutamine and protein-bound lysine residues, and (ii) cross-links between primary amines and protein-bound glutamine (Nurminskaya and Belkin, 2012).…”
Section: In Vitro Modulation Of Tg2 Transamidation Activity By the Pamentioning
confidence: 99%
See 3 more Smart Citations
“…TG2 can catalyse two types of transamidation, namely (i) intra-, and/or inter-molecular covalent cross-links between protein-bound glutamine and protein-bound lysine residues, and (ii) cross-links between primary amines and protein-bound glutamine (Nurminskaya and Belkin, 2012).…”
Section: In Vitro Modulation Of Tg2 Transamidation Activity By the Pamentioning
confidence: 99%
“…Our recent studies have shown that the Gi/o-protein coupled A1 adenosine receptor stimulates TG2 activation in H9c2 cardiomyocyte-like cells (Vyas et al, 2016). Since TG2 transamidase activity modulates protein function by cross-linking and incorporation of small molecule mono-and polyamines into protein substrates, it is likely that activation of TG2 by GPCRs plays a major role in the regulation of cellular function (Nurminskaya and Belkin, 2012;Eckert et al, 2014).…”
Section: In Vitro Modulation Of Tg2 Transamidation Activity By the Pamentioning
confidence: 99%
See 2 more Smart Citations
“…Once Ca 2+ binds to TG, a cysteine is exposed leading to the formation of a bond between ε-amide (as an isodipeptide or polyamine bond) and γ-carboxamide of protein bound glutamine residues [1]. Transglutaminase 2 (TG2), the most widely studied member of the TG family, has been implicated in the regulation of a wide range of processes, including cell adhesion, migration, growth, survival, apoptosis, differentiation, and extracellular matrix organization [2]. The role of TG2 in cell survival and cell death is cell-specific with respect to whether it has pro-or anti-apoptotic effects [3].…”
Section: Introductionmentioning
confidence: 99%